Upper gastrointestinal acute graft-versus-host disease adds minimal prognostic value in isolation or with other graft-versus-host disease symptoms as currently diagnosed and treated - Sarah Nikiforow; Tao Wang; Michael Hemmer; Stephen Spellman; Görgün Akpek; Joseph H. Antin; Sung Won Choi; Yoshihiro Inamoto; Hanna J. Khoury; Margaret MacMillan; David I. Marks; Ken Meehan; et al. (Haematologica, 2018)
Upper gastrointestinal acute graft-versus-host disease is reported in approximately 30% of hematopoietic stem cell transplant recipients developing acute graft-versus-host disease. Currently classified as Grade II in consensus criteria, upper gastrointestinal acute graft-versus-host disease is often treated with systemic immunosuppression. We reviewed the Center for International Blood and Marrow Transplant Research database to assess the prognostic implications of upper gastrointestinal acute graft-versus-host disease in isolation or with other acute graft-versus-host disease manifestations. 8567 adult recipients of myeloablative allogeneic hematopoietic stem cell transplant receiving T-cell replete grafts for acute leukemia, chronic myeloid leukemia or myelodysplastic syndrome between 2000 and 2012 were analyzed. 51% of transplants were from unrelated donors. Reported upper gastrointestinal acute graft-versus-host disease incidence was 12.1%; 2.7% of recipients had isolated upper gastrointestinal acute graft-versus-host disease, of whom 95% received systemic steroids. Patients with isolated upper gastrointestinal involvement had similar survival, disease-free survival, transplant-related mortality, and relapse as patients with Grades 0, I, or II acute graft-versus-host disease. Unrelated donor recipients with isolated upper gastrointestinal acute graft-versus-host disease had less subsequent chronic graft-versus-host disease than those with Grades I or II disease (P=0.016 and P=0.0004, respectively). Upper gastrointestinal involvement added no significant prognostic information when present in addition to other manifestations of Grades I or II acute graft-versus-host disease. If upper gastrointestinal symptoms were reclassified as Grade 0 or I, 425 of 2083 patients (20.4%) with Grade II disease would be downgraded, potentially impacting the interpretation of clinical trial outcomes. Defining upper gastrointestinal acute graft-versus-host disease as a Grade II entity, as it is currently diagnosed and treated, is not strongly supported by this analysis. The general approach to diagnosis, treatment and grading of upper gastrointestinal symptoms and their impact on subsequent acute graft-versus-host disease therapy warrants reevaluation.